Comparison of Fibrinogen Level Changes between Pregnancy with History of Abortion and Normal Pregnancy - Robbi A. Wicaksono (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To know the change of fibrinogen level in pregnancy with history of abortion and normal pregnancy on 6 - 8 weeks pregnancy and 10 - 12 weeks pregnancy. Method: This is a comparative study analytic comparative with cross sectional method on both groups, pregnancy with history of abortion and normal pregnancy. Observe the changes of fibrinogen level on 6 - 8 weeks pregnancy and then on 10 - 12 weeks pregnancy in pregnancy with history of abortion and normal pregnancy. Result: Comparison of mean fibrinogen level between 6 - 8 weeks pregnancy and 10 - 12 weeks pregnancy, on both group showed that the fibrinogen level in the group with history of abortion increased 9.6% and in the group of normal pregnancy increased 11.4%. The raise on both group was not significant stastistically (p = 0.810). The raise fibrinogen level on normal pregnancy was significant (p < 0.001), while on pregnancy with history of abortion is not significant (p = 0.255). All patterns of raise and fall on fibrinogen level on both groups were not stastistically significant (p > 0.005). Conclusion: Fibrinogen level on 10 - 12 weeks pregnancy was not lower than on 6 - 8 weeks pregnancy in pregnancy with history of abortion. There was no significant raise changes in fibrinogen level on both groups. [Indones J Obstet Gynecol 2011; 35-2: 53-6] Keywords: abortion, fibrinogen, haemostasis, history of abortion, normal pregnancy